Analysis of epidemiological profile and ventilator parameters of puerperas submitted to mechanical ventilation by electrical impedance tomography - Gerhardt, Nayara Oliveira Lima; Oliveira, Thayssa Costa de; Almeida, Ingrid da Costa Noronha de; Oliveira, Rosângela Leão; Neves, Pablo Fabiano Moura das; Silva, Pablo Apoena Ramos Gomes da; Ferreira, Reinaldo Luiz da Silva; Avila, Paulo Eduardo Santos (ABCS Health Sciences, 2020)
Introduction: Pregnancy-related diseases have aggravated the situation of postpartum women, who end up using Mechanical Ventilation (MV) when admitted to Intensive Care Units (ICU). Although VM has benefits, it is associated with deleterious effects that can be minimized with the use of Electrical Impedance Tomography (EIT). Objective: The aim was analyze the epidemiological profile and ventilatory parameters of mothers, which developed HELLP Syndrome, Sepsis and/or Acute Respiratory Distress Syndrome (ARDS), under MV and monitored with EIT. Methods: The study was observational, retrospective and prospective cross-sectional, conducted between March and September 2018, using data collection forms filled from a sociodemographic, obstetric and ventilatory database of postpartum women admitted to an adult ICU. Results: Sample consisting of 13 puerperal women, 8 with sepsis (61.5%), 7 with HELLP syndrome (53.8%) and 4 with ARDS (30.8%), demonstrating that 5 patients (38.5%) evolved with more than one of these pathologies. Regarding the ventilatory parameters evaluated, VT 378.9 (± 103.9) were observed and mean values found for PEEP 9.8 (±1.9) and driving pressure 11.1 (±1.4) are below those recommended by the literature, predicting lower mortality and morbidity index. Conclusion: The relevance of the driving pressure assessment in the MV setting was demonstrated, a parameter assessed by the EIT and directly related to Cstat, PEEP, VT and optimization of regional pulmonary ventilation. We highlight the need for future research that presents greater clinical significance regarding the profile of postpartum women in relation to the increasingly frequent diseases in this population.